Policy Implementation of Luwu Regional Library Development Policy - Mallappiang, Nasiratunnisaa; Agustang, Andi; Idkhan, Andi Muhammad (PINISI Discretion Review, 2022)
This study aims to measure the implementation of regional library development service policies in Luwu Regency based on 4 indicators, namely: development and arrangement of library service systems, promotion of library services and promotions, development of future library services, and development of integrated service systems with libraries and information centers. This study uses a quantitative method with non-probability sampling technique that is exploratory, the determination of the sample is carried out by purposive sampling involving 194 respondents consisting of: Regional Librarians. Campus/School/Mosque Librarians, Community Reading Park Librarians (TBM), Village Library Librarians, Literacy Activists, and Library Visitors. The results showed that the development and arrangement of the library service system was in good category, namely 55%, service promotion and library promotion was in good category, 57%, future library service development was in good category, which was 52%, and the development of integrated service system with libraries and information centers was in the good category. good that is 56%.